Izobraževanje visokošolskih učiteljev s posebnim poudarkom na sobotnem letu - Tancer Verboten, Mojca (Annales. Series historia et sociologia, 2021)
The right and duty of a higher education teacher, which is determined by law, is continuous education, improvement and training as required by the needs of the working process, with the aim of maintaining or expanding the ability to perform work under an employment contract, maintaining employment. Didactic training is specific to a higher education teacher. Universities in Slovenia have an indirect requirement for training in the field of pedagogical and andragogical knowledge determined in internal acts, namely candidates in the process of election to the title must demonstrate pedagogical competence, but no special certificates of didactic competence are required. Given the changing system of study, i.e. partial relocation of pedagogical responsibilities, it would make sense to reintroduce the obligation for higher education teachers to attend didactic training. As a special right to further training, the possibility of using the Sabbatical is provided for higher education teachers at the university. The statutory right to a Sabbatical is the norm of the lex imperfecta because it has no sanction. The use of the institute on Sabbatical brings many open questions, which are now left to the autonomous regulation of universities, but it would be appropriate to regulate the minimum framework and funding at the legislative level.
Keywords: education; further training; higher education teachers; izobraževanje; izpopolnjevanje; Sabbatical; sobotno leto; specific training of higher education teachers; specifična usposabljanja visokošolskih učiteljev; visokošolski učitelji